Do "white knights" make excessive profits in bank resolution? - Florian Heider; Jonas Schlegel; Tobias Tröger; Mark Wahrenburg (Leibniz Institute for Financial Research SAFE, 2023)
This study looks at potential windfall profits for the four banking acquisitions in 2023. Based on accounting figures, an FT article states that a total of USD 44bn was left on the table. We see accounting figures as a misleading analysis. By estimating marked-based cumulative abnormal returns (CAR), we find positive abnormal returns in all four cases which when made quantifiable, are around half of the FT's accounting figures. Furthermore, we argue that transparent auctions with enough bidders should be preferred to negotiated bank sales. This document was provided/prepared by the Economic Governance and EMU Scrutiny Unit at the request of the ECON Committee.
Keywords: 330; Bank Resolution; Bank Acquisition; Auctions; "Event Study"